ON NECESSITY FOR CREATION OF TECHNOLOGICAL MACHINERY SYSTEM IN CONSTRUCTION COMPLEX - A. V. Vavilov (Наука и техника)
The paper substantiates the necessity for creation of a technological machinery system in multi-industry construction complex that is from development of raw material resources and production of construction materials (logging and mining industry, woodworking, production of crushed stone, cement, concrete etc.) to construction of actual 3D and plate objects. Attention has been attracted to continuous renovation of construction technologies and emergence of new construction materials that requires corresponding technical facilities for their efficient application and creation of these facilities is lagging behind under existing conditions. Such approach leads to saturation of the Republican machinery park by import equipment and technology that correspond to introduced technologies and construction materials according to their parameters.In order to ensure success in import substitution it is necessary to create a prospective system of technological machinery that corresponds to new technologies and materials. Experience in creation of separate fragments of the machinery system reveals machinery similarity irrespective of construction complex sector. Such approach permits to create multi-functional technical facilities having not only similar basic machines but key equipment as well that differs only in design of finite element of working tool. It has been established that multi-functionality favours a significant reduction in financial expenses for renovation of machinery parks and an increase of modular machine number. It has been shown that the machinery system prompts in due time what technical facilities are to be created in order to realize non-waste technologies in the construction complex which are completed by production of certain useful products.